The fate of monocytes in atherosclerosis - Randolph, Gwendolyn (Henry Stewart Talks, 2009)
Initiation of atherosclerosis and importance of monocytes, Description of monocyte subsets, Tracking of monocyte subsets into plaques, Macrophage subtypes and possible relevance to atherosclerosis, CX3CR1 in atherosclerosis |Resolution of inflammation and its failure in atherosclerosis